(untitled) (Praxis Educativa, 2012)
Philippe Meirieu’s pedagogical thought presents three great periods: learning, philosophical reflection on autonomy and freedom and a critical-political insight into citizens’ education. The extensive work of this French pedagogue compels us, in this paper, to turn our attention to the relationship between learning and pedagogy. Learning belongs to the first period of his intellectual development. As a result of our research on the concept of pedagogy in Meirieu’s work we were able to identify some aspects in the above mentioned relationship, especially his ideas about groups, educability, means, learning as pedagogical physics and learning models. In conclusion, the purpose of this text is to contribute to a reflection on pedagogy as a fundamental concept of French educational science and particularly, to focus on a contemporary pedagogue’s way of narrating.